Chewing and Cognitive Improvement: The Side Matters - Tramonti Fantozzi, Maria Paola; De Cicco, Vincenzo; De Cicco, Davide; d’Ascanio, Paola; Cataldo, Enrico; Bruschini, Luca; Faraguna, Ugo; Manzoni, Diego (Frontiers in Systems Neuroscience, 2021)
Chewing improves cognitive performance, which is impaired in subjects showing an asymmetry in electromyographic (EMG) masseter activity during clenching. In these subjects, the simultaneous presence of an asymmetry in pupil size (anisocoria) at rest indicates an imbalance in Ascending Reticular Activating System (ARAS) influencing arousal and pupil size. The aim of the present study was to verify whether a trigeminal EMG asymmetry may bias the stimulating effect of chewing on cognition. Cognitive performance and pupil size at rest were recorded before and after one minute of unilateral chewing in 20 subjects with anisocoria, showing an EMG asymmetry during clenching. Unilateral chewing stimulated performance mainly when it occurred on the side of lower EMG activity (and smaller pupil size). Following chewing on the hypotonic side, changes in cognitive performance were negatively and positively correlated with those in anisocoria and pupil size, respectively. We propose that, following chewing on the hypotonic side, the arousing effects of trigeminal stimulation on performance are enhanced by a rebalancing of ARAS structures. At variance, following chewing on the hypertonic side, the arousing effect of trigeminal stimulation could be partially or completely prevented by the simultaneous increase in ARAS imbalance.